2022
DOI: 10.3389/fnins.2022.825172
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Functional Magnetic Resonance Imaging Signal Complexity Across Multiple Time Scales in Patients With Migraine Without Aura

Abstract: BackgroundMigraine is a primary neurological disorder associated with complex brain activity. Recently, mounting evidence has suggested that migraine is underpinned by aberrant dynamic brain activity characterized by linear and non-linear changes across a variety of time scales. However, the abnormal dynamic brain activity at different time scales is still unknown in patients with migraine without aura (MWoA). This study aimed to assess the altered patterns of brain activity dynamics over different time scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Additionally, studies had found that female migraineurs exhibited reduced GMV in the ACC and prefrontal cortex, which is consistent with the findings of the present study( Dai et al. 2015 ; Wang et al. 2022a ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, studies had found that female migraineurs exhibited reduced GMV in the ACC and prefrontal cortex, which is consistent with the findings of the present study( Dai et al. 2015 ; Wang et al. 2022a ).…”
Section: Discussionsupporting
confidence: 93%
“…Our current findings showed increased FC between the anterior part of ACC (sACC and pACC) and middle DMN (MTG), and decreased FC between the sACC and SN (ACG). Our previous study showed abnormalities in the ACC-DMN pattern network in patients with MM ( Wang et al. 2022a ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Neuroimaging confirmed that acupuncture can be integrated into pain-related brain regions through different neural afferent pathways that cause analgesic effects. [22][23][24] Experimental studies have found that the mechanism of acupuncture for migraine involves inhibiting neurogenic inflammation, improving cerebral microcirculation, [25] and regulating vasoactive substances. [26,27] Animal experiments using a rat model of migraine have confirmed that electroacupuncture can inhibit hyperalgesia by decreasing the number of mast cells and macrophages and serum levels of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%